IMPLEMENTATION OF BLENDED LEARNING MODEL BASED ON NSTU DISTANCE LEARNING SYSTEM - Marina V. Legan; Tatyana A. Yatsevich (Высшее образование в России)
The article describes the implementation of blended learning model by using distance learning system DiSpace 2.0. at NSTU. The advantages of NSTU LMS training materials (electronic educational and methodical complex for curricula disciplines) are discussed as well as recruitment problems for programs using distance technologies.